Differential impact of body mass index and leptin on baseline and longitudinal positron emission tomography measurements of the cerebral metabolic rate for glucose in amnestic mild cognitive impairment - Weise, Christopher M.; Chen, Kewei; Chen, Yinghua; Devadas, Vivek; Su, Yi; Reiman, Eric M. (Frontiers in Aging Neuroscience, 2022)
INTRODUCTION: Several studies have suggested that greater adiposity in older adults is associated with a lower risk of Alzheimer’s disease (AD) related cognitive decline, and some investigators have postulated that this association may be due to the protective effects of the adipose tissue-derived hormone leptin. In this study we sought to demonstrate that higher body mass indices (BMIs) are associated with greater baseline FDG PET measurements of the cerebral metabolic rate for glucose (CMRgl), a marker of local neuronal activity, and slower CMRgl declines in research participants with amnestic mild cognitive impairment (aMCI). We then sought to clarify the extent to which those relationships are attributable to cerebrospinal fluid (CSF) or plasma leptin concentrations. METHODS: We used baseline PET images from 716 73±8 year-old aMCI participants from the AD Neuroimaging Initiative (ADNI) of whom 453 had follow up images (6 months; mean follow up time 3.3 years). For the leptin analyses, we used baseline CSF samples from 81 of the participants and plasma samples from 212 of the participants. RESULTS: As predicted, higher baseline BMI was associated with greater baseline CMRgl measurements and slower declines within brain regions preferentially affected by AD. In contrast and independently of BMI, CSF and plasma leptin concentrations were mainly related to less baseline CMRgl within mesocorticolimbic brain regions implicated in energy homeostasis. DISCUSSION: While higher BMIs are associated with greater baseline CMRgl and slower declines in persons with aMCI, these associations appear not to be primarily attributable to leptin concentrations.